Modernizing Zakat in Indonesia, from Masdar Farid Mas'udi, Safwan Idris, and Didin Hafidhuddin - Nasution, Juliana; Nasution, Muhammad Idris; Murtadla, Abdullah Alfikri (Universitas Muhammadiyah Surakarta, 2024)
Zakat as a scientific and teaching discourse has undergone modernization. However, the pattern of modernization itself is not uniform. This article will describe three patterns of efforts to modernize zakat in Indonesia through the thoughts of three figures, namely Masdar Farid Mas'udi, Safwan Idris and Didin Hafidhuddin. This research is qualitative and literary in nature in the scope of studying figures' thoughts using a historical-sociological approach. Data was taken from the three main books of the figures, then analyzed using descriptive, synthetic and comparative analysis techniques which focused on categorical analysis. The results of this research show that the three figures offer modernization of zakat related to understanding the concept of zakat, sources of zakat, distribution of zakat, the relationship between tax and zakat, and modernization of zakat institutions. Masdar modernized zakat by reconstructing the concept of zakat, by reconstructing the concepts of qath'i-zhanni and sunnah-hadith. The criticism is mainly related to taxes, which do not have the spirit of zakat. Safwan Idris is trying to reform the management of zakat and understand zakat as sunnatullah, not as sunnatul-insan. Didin Hafidhuddin responded to the modernization of zakat by expanding zakat sources based on a modern economy. Their thoughts are quite relevant in the current development of zakat management in Indonesia, although not all of their thoughts have been accommodated.